Natural ventilation in London: Towards energy-efficient and healthy buildings. (15th May 2021) - Song, Jiyun; Huang, Xinjie; Shi, Dachuan; Lin, William E.; Fan, Shiwei; Linden, Paul F.
Abstract: Natural ventilation (NV) is a sustainable solution to improve building energy efficiency and reduce carbon emission. In this study, we quantified the impact of air pollution and noise pollution on the NV potential at both city scale and building scale in London. At city scale, the loss of annual cooling energy saving potential due to noise pollution (8.1 kWh/m 2 ) was found to be comparable to that due to air pollution (9.0 kWh/m 2 ). At building scale, we selected a naturally ventilated office building in central London with two windows facing a noisy and polluted traffic road and one window overlooking a quiet and clean courtyard for case study. By coupling EnergyPlus simulation with advanced wind tunnel experiments, we identified the prevailing inflow directions and cooling energy saving potentials of 26 NV modes with different window combinations. It was found that cross ventilation with stack effects is the most efficient NV mode for indoor-outdoor exchanges and prevailing building inflow direction can be regulated by optimising window openings at different heights. Particularly for the case study building, we can save cooling energy by up to 5.6 kWh/m 2 per month in the optimal NV mode while minimising the negative health impact of ambient pollution by introducing more fresh air from the cleaner side. In addition, local urban morphological changes such as the presence of a tall building or the expansion of an adjacent road were also found to be influential on NV performances. Highlights: The impact of air and noise pollution on natural ventilation potential was quantified at both city and building scales. The prevailing inflow directions were identified by coupling EnergyPlus model with advanced wind tunnel experiments. Window optimisation strategies were proposed by considering the trade-offs between energy efficiency and health impact. An additional 20 kWh/m 2 can be saved per annum via natural ventilation upon further reduction of air and noise pollution.